Determinant Factors Of Environmental Accounting, Empirical Studies On Manufacturing Industries Listed On The Indonesia Stock Exchange - Stevanus Antoni R; Febriana Eka Safitri; Siska (International Conference On Law And Social Sciences, 2024)
This research aims to determine the influence of financial performance, company size, and capital structure on the disclosure of environmental accounting information in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2018-2020 period. This research uses secondary data obtained from financial reports published by the Indonesia Stock Exchange (BEI) via www.idx.co.id and the company website. The population in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange, consisting of 67 companies. Sampling was carried out using the purposive sampling method. The analytical method used is multiple linear regression analysis. The research results show that financial performance influences the disclosure of environmental accounting information, company size and capital structure do not influence the disclosure of environmental accounting information. However, financial performance, company size, and capital structure simultaneously influence the disclosure of environmental accounting information.